Spatial Variability and Analysis of Key Soil Properties in the Kesem Irrigation Scheme, Awash River Basin, Ethiopia - Jiru, Mengistu; Mekonnen, Boja; Henk, Ritzema; Abegaz, Fentaw (MO.RI Publishing, 2025)
The Kesem Irrigation Scheme, located in the middle Awash River Basin of Ethiopia faces significant challenges due to widespread soil salinity and sodicity, hindering its agricultural productivity. This study aims to assess the spatial distribution and extent of soil salinity and evaluate the spatial variability of key soil properties in southern block of the scheme, encompassing 5000 hectares. A total of 154 composite soil samples were collected from both active sugarcane fields and abandoned areas at 0-30 cm and 30-60 cm depths. Soil properties analyzed included particle size distribution, pH, electrical conductivity (ECe), exchangeable sodium percentage (ESP), and exchangeable cations. Geostatistical analysis, including semivariogram modeling and ordinary kriging, was employed to assess the spatial variability of soil properties. Descriptive statistics, normality tests, and paired t-tests were performed. Soil textural classes were determined, and soil salt classes were classified based on ECe, ESP, and pH Soil texture analysis revealed a predominance of silt and clay fractions, while soil assessment identified four salt classes: non-saline, saline, saline-sodic, and alkaline based on FAO techniques. Results showed that pH had the lowest coefficient of variation (CV), while the ECe had the highest CV. Variability was generally greater in the bottom layer, except for cation exchange capacity (CEC) and ESP. Prosopis Julifera-infested areas had substantially lower ECe and ESP, with increased pH. Geostatistical analysis showed moderate to strong spatial dependence for most soil properties within a range of 861-6186 meters. The dominance of silt-dominated soils increases the risk of sodium retention, exacerbating salinity and sodicity issues. Elevated salinity and sodicity levels were observed in certain areas, attributed to factors such as groundwater table rise and inadequate drainage. This study provides valuable information for developing site-specific soil management strategies to enhance agricultural productivity and ensure sustainable agricultural land use. Further research is essential to determine the specific roles of various soil salinity factors in influencing soil properties within irrigated agricultural systems.